2022
DOI: 10.1021/acsomega.2c00535
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib-Containing Dual Conjugates Targeting αVβ6 Integrin and Tyrosine Kinase Receptors as Potential Antifibrotic Agents

Abstract: α V β 6 Integrin plays a fundamental role in the activation of transforming growth factor-β (TGF-β), the major profibrotic mediator; for this reason, α V β 6 ligands have recently been forwarded to clinical phases for the therapy of fibrotic diseases. Herein, we report the synthesis and in vitro biological evaluation as antifibrotic agents of three new covalent conjugates, constituted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…As stated above, our previous experiments on both sunitinib and nintedanib conjugates of type I and II clearly demonstrated that the tyrosine kinase inhibitory (TKI) activity of the drug portion was maintained, as proven by in vitro assays on isolated human recombinant VEGFR [30,33] . Given the structural resemblance between those compounds and conjugates 1 – 3 in this study, we also logically expected preservation of their TKI activity.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…As stated above, our previous experiments on both sunitinib and nintedanib conjugates of type I and II clearly demonstrated that the tyrosine kinase inhibitory (TKI) activity of the drug portion was maintained, as proven by in vitro assays on isolated human recombinant VEGFR [30,33] . Given the structural resemblance between those compounds and conjugates 1 – 3 in this study, we also logically expected preservation of their TKI activity.…”
Section: Resultssupporting
confidence: 61%
“…As stated above, our previous experiments on both sunitinib and nintedanib conjugates of type I and II clearly demonstrated that the tyrosine kinase inhibitory (TKI) activity of the drug portion was maintained, as proven by in vitro assays on isolated human recombinant VEGFR. [30,33] Given the structural resemblance between those compounds and conjugates 1-3 in this study, we also logically expected preservation of their TKI activity. Of course, since nintedanib binds to the intracellular region of growth factor receptors, the in-cell TKI activity of compounds 1-3 may be appreciably detected, provided that cell internalization occurs even if only partially.…”
Section: Cell Internalization Studiesmentioning
confidence: 84%
See 3 more Smart Citations